(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The word Jharkhand is a combination of two Hindi words ‘jhar’ and ‘khand’. ‘jhar’ means apretty thick cluster of forest and ‘khand’ means a tract of land. Thus Jharkhand suggest of land massquilted with forest. To study the scenario, impact of population growth and its impact on socioeconomicdevelopment of the state of Jharkhand, all possible methods and techniques of reasons wereadopted. The population of Jharkhand is growing rapidly. The impact of rising population on socio-Economic development of Jharkhand is quite significant, as standard of living of a common man is notimproving. Jharkhand state in India is basically administrative and for implementation of measures tocontrol the rapid increase in population which create problem in the development of our country as wellas the state.